Cr(VI) reduction, electricity production, and microbial resistance variation in paddy soil under microbial fuel cell operation - H. Niu; C. Wang; X. Luo; P. Li; H. Qiu; L. Jiang; S. Maimaitiaili; M. Wu; F. Xu; H. Xu (SOIL)
The microbial fuel cell (MFC) is an efficient in situ approach to combat pollutants and generate electricity. This study constructed a soil MFC (SMFC) to reduce Cr(VI) in paddy soil and to investigate its influence on microbial community and microbial resistance characteristics. Ferroferric oxide (Fe3O4) nanoparticles, as the cathodic catalyst, effectively boosted power generation (0.97 V, 102.00 mW m−2), with the porous structure and reducibility also contributing to chromium (Cr) reduction and immobilization. After 30 d, 93.67 % of Cr(VI) was eliminated. The bioavailable Cr decreased by 97.44 %, while the residual form increased by 88.89 %. SMFC operations greatly changed soil enzymatic activity and microbial structure, with exoelectrogens like Desulfotomaculum (3.32 % in the anode) and Cr(VI)-reducing bacteria like Hydrogenophaga (2.07 % in the cathode) in more than 1000 folds of soil. In particular, SMFC operations significantly enhanced heavy-metal resistance gene (HRG) abundance. Among them, chrA, chrB, and chrR increased by 99.54 %–3314.34 % in SMFC anodes, probably attributable to the enrichment of potential tolerators like Acinetobacter, Limnohabitans, and Desulfotomaculum. These key taxa were positively correlated with HRGs but were negatively correlated with pH, electrical conductivity (EC), and Cr(VI), which could have driven Cr(VI) reduction. This study provided novel evidence for bio-electrochemical system applications in contaminated paddy soil, which could be a potential approach for environmental remediation and detoxification.